Factors Affecting the Attractive Force of Dental Magnetic Attachment: A Literature Review for Guiding Dentists in Clinical Application - An-Nissa Kusumadewi; Lisda Damayanti; null Rukiah; null Risdiana (International Journal of Dentistry)
Aim. The aim of this review is to get a comprehensive description of the factors that may influence the attractive force of the dental magnetic attachment. Background. Dental magnetic attachment is a term for a magnet used as an overdenture retainer. Magnets that are widely used are permanent magnets such as neodymium iron boron (NdFeB) and samarium cobalt (SmCo). Theoretically, the magnetic attractive force in a permanent magnet has a constant retentive force, and the magnitude of the force will not decrease over time. However, several studies revealed that the magnetic attractive force can be decreased, resulting in the failure of overdenture retention. Some of the factors of reduced magnetic attraction that have been studied are corrosion and temperature. There are no articles that specifically review the factors that can influence magnetic attraction. Review Results. A total of 25,880 articles were obtained during a search on 3 journal databases: PubMed (2,647), ScienceDirect (23,184), and Scopus (229). From those publications, 15 articles reported relevant outcome data that were then extracted. Magnetic attractive force can be influenced by temperature, corrosion, keeper surface morphology, type of magnet, keeper-assembly size combination, inclination, insertion-removal cycle, gliding/loading cycle, number of magnets, crosshead speed, and force direction. Conclusion. Many factors can affect the magnetic attraction force of the dental magnetic attachment. Corrosion is the most likely factor to occur because the dental magnetic attachment is always in the oral environment which contains corrosive saliva and is susceptible to damage due to mastication forces.